2010
DOI: 10.3109/17482968.2010.539235
|View full text |Cite
|
Sign up to set email alerts
|

FUS/TLSgene mutations are the second most frequent cause of familial ALS in the Spanish population

Abstract: information on 85 patients in the 25 families studied, although there were approximately 144 affected individuals across four or fi ve generations in 60% of the families. The mean number of affected individuals per family was 5.7. Of the 30 families, fi ve had mutations in SOD1 (20), and mutations in FUS/TLS were identifi ed in two.Family F-19. The proband (IV:18) presented at 41 years of age for genetic screening. She had developed progressive weakness and wasting of the upper limbs (UL) over the preceding 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
7
14
1
Order By: Relevance
“…Mutations in SOD1 were present in 20.0% of fALS patients and 1.9% of sALS patients, which is consistent with previous studies in western populations8, and indicates that SOD1 mutations play a key role in the pathology of ALS patients from different ethnicities. In addition, the frequency of FUS mutation was approximately 13.3% in fALS patients, which is consistent with reports from several other populations11121314, but is higher than the frequencies found in Catalan (8%)15, German (2.4–6.9%)1617, Italian (4.4%)12, and Belgian (2.9%)18 populations. This difference may be due to small sample sizes and the differing ethnicities of fALS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Mutations in SOD1 were present in 20.0% of fALS patients and 1.9% of sALS patients, which is consistent with previous studies in western populations8, and indicates that SOD1 mutations play a key role in the pathology of ALS patients from different ethnicities. In addition, the frequency of FUS mutation was approximately 13.3% in fALS patients, which is consistent with reports from several other populations11121314, but is higher than the frequencies found in Catalan (8%)15, German (2.4–6.9%)1617, Italian (4.4%)12, and Belgian (2.9%)18 populations. This difference may be due to small sample sizes and the differing ethnicities of fALS patients.…”
Section: Discussionsupporting
confidence: 91%
“…An overview of clinical symptoms of all patients is given in (Blair et al, 2010;Syriani et al, 2011). One patient was reported to have a history of impaired mental development during childhood.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…One very interesting clinical feature observed in patients with a FUS mutation was a functionally disabling dropped-head syndrome, which emerged in two patients in the course of the disease and one patient even displayed it as the first symptom. This symptom had been described before in ALS patients carrying a FUS mutation (Blair et al, 2010;Syriani et al, 2011), while in "classical" ALS cases, it is not a common feature. Mental retardation or learning difficulties were described before in some patients with early-onset FUS-associated ALS (Zou et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
“…The first two reports suggested that FUS mutations might only be associated with FALS [Kwiatkowski et al, ; Vance et al, ]. However, several recent reports identified FUS mutations in SALS patients, including the most common variants p.R521C and p.R521H (Table ) [Belzil et al, ; Blair et al, ; Broustal et al, ; Chiò et al, ; Corrado et al, ; Drepper et al, ; Groen et al, ; Kwiatkowski et al, ; Lai et al, ; Millecamps et al, ; Rademakers et al, ; Sproviero et al, ; Suzuki et al, ; Syriani et al, ; Ticozzi et al, ; Tsai et al, ; van Blitterswijk et al, ; Vance et al, ; Van Damme et al, ; Van Langenhove et al, ; Yamamoto‐Watanabe et al, ; Yan et al, ; Zou et al, ].…”
Section: Fus Mutations In Alsmentioning
confidence: 99%